Evaluasi Fungsi Sistem Drainase Kawasanan Permukiman Kota Tolitoli (Studi Kasus Rt 001.002-Rw 005 Kelurahan Baru) - Mansur S Pahude (Jurnal Multidisiplin Madani, 2022)
In principle, roads in Tolitoli Regency have been equipped with a drainage system. From the results of the field survey, the data needed as a reference for evaluating the drainage system are obtained, namely the dimensions of the channel, the area of ​​the study area as primary data and land surface elevation, population data as secondary data. The data obtained were analyzed in order to obtain different soil surface heights, different heights at each point of the drainage channel, the dimensions of the current drainage channel along with the depth of sediment in the drainage channel, so that the cause of the malfunction of the drainage system can be determined. The cause of non-functioning drainage in urban residential areas is due to sedimentation at the bottom of the channel which causes drainage not optimal. So it is necessary to maintain the function of the existing drainage channels in urban residential areas so that they can function optimally.